2023
DOI: 10.3389/fpubh.2023.1183483
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in Chinese medical staff: a latent profile analysis

Abstract: ObjectiveTo investigate subgroups of health-related quality of life (HRQoL) in the Chinese medical staff and identify the demographic factors associated with these profiles.Methods574 Chinese medical staff were surveyed online. HRQoL was measured by using the 36-Item Short Form Health Survey, Version 2. Latent profile analysis (LPA) was used to identify the profiles of HRQoL. The associations between HRQoL profiles and covariates were assessed using multinomial logistic regression.ResultsThree HRQoL profiles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The demanding and stressful nature of healthcare professions poses a potential threat and can significantly influence the HRQoL of healthcare professionals. Moreover, the particular work environment and interpersonal dynamics can also have an impact on the HRQoL of medical personnel ( 27 ). The current study revealed that 54.6% of the study participants scored below the mean score of WHOQOL-BREF, indicating a poor quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The demanding and stressful nature of healthcare professions poses a potential threat and can significantly influence the HRQoL of healthcare professionals. Moreover, the particular work environment and interpersonal dynamics can also have an impact on the HRQoL of medical personnel ( 27 ). The current study revealed that 54.6% of the study participants scored below the mean score of WHOQOL-BREF, indicating a poor quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…This approach can enhance the overall quality of healthcare. Although several studies have examined HRQoL patterns among medical staff [ 19 ] and breast cancer patients [ 20 ], there is limited research on HRQoL among PWID [ 21 ]. Latent profile analysis (LPA) is a person-centered approach that can identify patterns or hidden subgroups based on individual responses from continuous data.…”
Section: Introductionmentioning
confidence: 99%
“…Latent profile analysis (LPA) is a person-centered approach that can identify patterns or hidden subgroups based on individual responses from continuous data. A previous study among 574 Chinese medical staff [ 19 ], which analyzed individual HRQoL responses, identified 3 distinct HRQoL patterns: high, moderate, and low HRQoL. To our knowledge, there is scant information on the patterns of HRQoL among PWID in Iran.…”
Section: Introductionmentioning
confidence: 99%